Student workbook to accompany Financial accounting : tools for business decision making - Weygandt, Jerry J. (John Wiley & Sons, 2000)
Introduction to financial statements. A further look at financial statements. The accounting information system. Accrual accounting concepts. Merchandising operations. Reporting and analyzing inventory. Internal control and cash. Reporting and analyzing receivables. Reporting and analyzing long-lived assets. Reporting and analyzing liabilities. Reporting and analyzing Stockholders' equity. Reporting and analyzing investments. Statement of cash flows. Financial analysis: the big picture.